Revision of the subgenus Metaeuops Legalov of Euops Schoenherr (Coleoptera, Curculionoidea, Attelabidae) from the Papuan region - Riedel, Alexander (Zootaxa, 2006)
The subgenus Metaeuops Legalov (stat.n.) of Euops Schoenherr is revised. The group is restricted to New Guinea and some small neighboring islands. It contains four previously described species: E. coelestinus Pascoe, E. ruficornis Voss, E. tibialis Voss, and E. violaceus Pascoe, and 14 new species: Euops arfakensis sp. n., E. biru sp. n., E. coeruleus sp. n., E. curvipes sp. n., E. illegalovi sp. n., E. judithae sp. n., E. oops sp. n., E. paratibialis sp. n., E. piceus sp. n., E. dintelmanni sp. n., E. ratcliffei sp. n., E. swartensis sp. n., E. tenuiflagellaris sp. n. and Euops torricelliensis sp. n.. Euops ruficornis Voss, formerly a subspecies of E. femoralis Voss, is recognized as a distinct species without any close relationship to E. femoralis Voss. Lectotypes are designated for E. coelestinus Pascoe, E. ruficornis Voss, E. tibialis Voss, and E. violaceus Pascoe. All species are described, and the characters relevant for their identification, especially the male genitalia, are illustrated. A key to the species is provided. A cladistic analysis is performed that confirms the monophyly of Metaeuops. The most important apomorphy of the group is a pair of sclerites in the mid portion of the male endophallus. Two additional characters imply secondary reduction in a few species: the subtriangular mesotibia of the males and a siphon-like extension of the female spermatheca. The original description of Metaeuops by Legalov contained contradictions between the diagnostic characters proposed and the characters present in the type species. Therefore, the concept of the genus is here modified.